1994
DOI: 10.1007/bf00039551
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of cucumber phosphoenolpyruvate carboxykinase and developmental regulation of gene expression

Abstract: A cDNA library from RNA of senescing cucumber cotyledons was screened for sequences also expressed in cotyledons during post-germinative growth. One clone encodes ATP-dependent phosphoenolpyruvate carboxykinase (PCK; EC 4.1.1.49), an enzyme of the gluconeogenic pathway. The sequence of a full-length cDNA predicts a polypeptide of 74,397 Da which is 43%, 49% and 57% identical to bacterial, trypanosome and yeast enzymes, respectively. The cDNA was expressed in Escherichia coli and antibodies raised against the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
1
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 28 publications
5
72
1
1
Order By: Relevance
“…In germinating seedlings and in senescing leaves, the glyoxylate cycle is associated with gluconeogenesis (Gut and Matile, 1988). The observation that glyoxylate cycle enzymes are induced, whereas PEP carboxykinase is not (Kim and Smith, 1994), suggested that in plant materials in which carbon export does not occur, the glyoxylate cycle may be used for biosyntheses other than gluconeogenesis. In a number of senescing or sugar-starved plant organs or cells, activities or mRNA amounts of malate synthase and isocitrate lyase, the two typical glyoxylate cycle enzymes, have been found to be increased (Graham et al, 1994, and refs.…”
Section: Does the Glyoxylate Cycle Play Any Role In Glc-starved Maizementioning
confidence: 99%
See 1 more Smart Citation
“…In germinating seedlings and in senescing leaves, the glyoxylate cycle is associated with gluconeogenesis (Gut and Matile, 1988). The observation that glyoxylate cycle enzymes are induced, whereas PEP carboxykinase is not (Kim and Smith, 1994), suggested that in plant materials in which carbon export does not occur, the glyoxylate cycle may be used for biosyntheses other than gluconeogenesis. In a number of senescing or sugar-starved plant organs or cells, activities or mRNA amounts of malate synthase and isocitrate lyase, the two typical glyoxylate cycle enzymes, have been found to be increased (Graham et al, 1994, and refs.…”
Section: Does the Glyoxylate Cycle Play Any Role In Glc-starved Maizementioning
confidence: 99%
“…it converts acetyl units to the four carbon organic acid succinate, thus allowing net biosyntheses from intermediates of the TCAC. In some cases, such as in senescing leaves, it appears to be linked with gluconeogenesis (Gut and Matile, 1988), but in detached leaves or in protoplasts, its function may be to provide four carbon precursors for amino acid synthesis (Graham et al, 1994;Kim and Smith 1994). In maize root tips only malate synthase was detected after starvation, and it was suggested that the role of this enzyme might be limited to the salvage of glyoxylate resulting from Gly catabolism (Dieuaide et al, 1992).…”
mentioning
confidence: 99%
“…It also shows that the part of the enzyme which is cleaved by proteolysis (which may be the N-terminal extension) either contains the phosphorylation site or is necessary for efficient phosphorylation of the remainder of the molecule. Within the N-terminal extension, Ser 67 and Thr 68 are likely target residues for phosphorylation because, apart from being within a consensus site for recognition by mammalian cAMPdependent protein kinase [19], they are also within a sequence of amino acids, Gln-Lys-Lys-Arg-Ser-Thr (residues 63-68) [4], which is similar to a proposed phosphorylation site motif for plant PEP carboxylase-kinase (Glu/Asp-Lys/Arg-X-X-Ser, for review see [12]). The phosphorylation of PEPCK was reversible.…”
Section: In Vitro Phosphorylation Of Pepckmentioning
confidence: 99%
“…In cucumber, the gene for PEPCK codes for a protein with a predicted molecular mass of about 74 kDa [4]. All previous purifications of the enzyme from C3 and C4 plants have yielded an enzyme with a molecular mass of between 62 and 64 kDa [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation